MEKANISME PENCATATAN ANGGARAN DANA DESA BERDASARKAN PELAPORAN STANDAR AKUNTANSI KEUANGAN TAHUN 2015 DI DESA TAROBOK - Harlina Liong (AkMen JURNAL ILMIAH, 2018)
The purpose of this study is to find out whether financial staff and Tarobok Village office employees already understand the mechanism of recording financial statements using Financial Accounting Standards (SAK). And to know the financial records Tarobok Village can be adjusted with Financial Accounting Standards (SAK). Based on the results of the analysis shows that the recording on the Village Fund Budget is still not in accordance with the applicable Financial Accounting Standards in Indonesia either the funds coming in or funds that will be allocated to villages for village development so that the authors make a research proposal appropriate financial reporting mechanism using Financial Accounting Standards. From this research proposal is expected to be applied to Tarobok Village for the basis of improvement so that the recording at the time of transaction of incoming fund or fund which will be allocated to villages for rural development.